Mean platelet volume predicts survival in patients with hepatocellular carcinoma and type 2 diabetes. (May 2019) - Yin, Ji-bin; Niu, Ye; Qian, Li-yan; Zhang, Xin; Liu, Zhi-ping; Wang, Rui-tao
Highlights: HCC patients with T2DM have a poorer prognosis relative to their non-diabetic counterparts. The patients with T2DM had lower MPV levels than patients without T2DM. Furthermore, MPV was found to be significantly associated with differentiation T2DM from non-T2DM. The overall survival of patients with low MPV levels was significantly shorter than that of those with high MPV levels in diabetic patients. Reduced MPV was a prognostic factor for poor outcome in HCC patients with T2DM. Abstract: Background: Patients with hepatocellular carcinoma (HCC) having pre-existing type 2 diabetes (T2DM) have a poorer prognosis than those without T2DM. Moreover, accumulating evidence reveals that activated platelets play a crucial role in tumor and T2DM. The mean platelet volume (MPV) indicates platelet activation and is altered in malignancies. The present study aimed to investigate the clinical significance of MPV in patients with HCC having T2DM. Methods: This retrospective study performed between January 2010 and December 2013 included 331 patients with HCC (165 with T2DM and 166 without T2DM). The overall survival was compared, and the predictors of overall survival were analyzed. Results: The patients with T2DM had lower MPV levels than those without T2DM. Furthermore, the MPV levels significantly differentiated T2DM from non-T2DM. In addition, for patients with T2DM, the overall survival was significantly shorter in patients with low MPV levels than in those with high MPV levels. Multivariate analysis identified decreased MPV as an independent prognostic factor for overall survival only in patients with T2DM, but not in those without T2DM. Conclusion: Reduced MPV was a prognostic factor for poor outcome in patients with HCC and T2DM.